2020
DOI: 10.1089/ten.tea.2019.0273
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Porcine Small Intestine Submucosa Nerve Cap for Prevention of Neuromas and Associated Pain

Abstract: Painful neuroma formation is a common and debilitating sequela of traumatic or oncologic nerve amputations. Studies suggest that isolating transected nerve stumps within protective caps during amputation surgery or revision procedures may assist in preventing symptomatic nerve-end neuroma formation. This study evaluated the local effects of two porcine small intestine submucosa (pSIS) nerve caps of differing configurations on a terminal nerve end in an animal model. The tibial nerves of 57 Sprague Dawley rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…S1a). This is in consistent with previous studies, whereby SIS nerve guidance conduits (NGCs) stably maintained their shape without collapsing for up to 8 weeks [ 46 ] and showed minimal-to-mild resorption by up to 12 weeks following implantation in vivo [ 47 ]. Immunofluorescence (IF) studies indicated that those transplanted GMSCs integrated into the wall matrix of NPs and localized in the peripheral areas outside of the injured nerves as recognized by the positive expression of human nuclei, whereas only about 5% of them were positively stained for the active form of caspase-3 (Additional file 1 : Fig.…”
Section: Resultssupporting
confidence: 92%
“…S1a). This is in consistent with previous studies, whereby SIS nerve guidance conduits (NGCs) stably maintained their shape without collapsing for up to 8 weeks [ 46 ] and showed minimal-to-mild resorption by up to 12 weeks following implantation in vivo [ 47 ]. Immunofluorescence (IF) studies indicated that those transplanted GMSCs integrated into the wall matrix of NPs and localized in the peripheral areas outside of the injured nerves as recognized by the positive expression of human nuclei, whereas only about 5% of them were positively stained for the active form of caspase-3 (Additional file 1 : Fig.…”
Section: Resultssupporting
confidence: 92%
“…21,22 Commercially available nerve capping devices made of synthetic or biological degradable materials are intended to provide protection from the tissue injury inflammatory environment. 8,9 While these devices can provide a macrostructural template to contain axonal regeneration, they can also create nerve "compartment syndrome" as they can become a "barrier/trap" for growing/sprouting axons. Furthermore, the degradation products of the synthetic material used for one of these technologies (PLLA-PCA) has been associated with a fibrotic inflammatory response, which can further increase the risk of neuroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…These devices can be made of synthetic or biologic materials and appear to attenuate painful neuroma formation, potentially by isolating free sensitized axons. While the cap devices have shown promising results in preclinical studies, 8,9 they have yet to be widely adopted, as the limited clinical evidence available suggests that nerve capping remains inferior to existing surgical approaches 7 . Recent studies have demonstrated that application of an acellular allograft provides a template for termination of the axonal growth potential within the length of the device 10 ; while this approach has shown promise, the length (i.e., 5 cm) of allograft required to exhaust the regenerative potential of the injured nerve creates the need for a more extensive surgical site 11 …”
Section: Introductionmentioning
confidence: 99%
“…5 When no viable distal nerve target is available (eg, amputation), the surgical approach to prevent neuroma formation often focuses on inhibiting axonal regrowth from the injured proximal nerve stump. Mechanisms studied to prevent disorganized axonal regrowth include implantation of the proximal nerve stump into adjacent tissue, [6][7][8][9] nerve coaptation, [10][11][12][13] nerve conduits, [14][15][16][17][18] and nerve capping, [19][20][21][22][23][24] with mixed results.…”
Section: Introductionmentioning
confidence: 99%